IMPLEMENTASI PERATURAN DAERAH NO 13 TAHUN 2021 TENTANG KETERTIBAN UMUM DAN KETENTERAMAN MASYARAKAT TERHADAP PENGATUR LALU LINTAS JALAN DI KOTA PEKANBARU TAHUN 2022 - Zalni, Bela Ratina; ', Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the implementation of Regional Regulation No. 13 of 2021 concerning Public Order and Community Peace towards road traffic controllers in Pekanbaru City in 2022. As a form of implementation of Regional Regulation No. 13 of 2021, the Pekanbaru City Satpol PP carries out control over traffic controllers road because they regulate traffic at every U-turn on the road with the intention of getting monetary rewards. The problem in this research is that there are still many road traffic controllers (Pak Ogah) at every U-turn in Pekanbaru City which causes traffic jams so that the implementation of Regional Regulation No. 13 of 2021 is not optimal. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out using interviews and documentation. The results of this research indicate that the implementation of Regional Regulation No. 13 of 2021 on road traffic controllers is not yet optimal, there are obstacles to communication between Satpol PP and road traffic controllers due to the absence of socialization, there are obstacles to the basic abilities of Satpol PP personnel, there are still lack of means to carry out control, there is still a lack of strategy and consistency in controlling road traffic so that road traffic control at every U-turn in Pekanbaru City continues to increase, and there is still a lack of role from the community. Keywords: Implementation of Regional Regulations, Controlling, Road Traffic Control